Tandem Androgenic and Psychological Shifts in Male Reproductive Effort Following a Manipulated “Win” or “Loss” in a Sporting Competition - Longman, Daniel P. (Hum Nat, 2018)
Male-male competition is involved in inter- and intrasexual selection, with both endocrine and psychological factors presumably contributing to reproductive success in human males. We examined relationships among men’s naturally occurring testosterone, their self-perceived mate value (SPMV), self-esteem, sociosexuality, and expected likelihood of approaching attractive women versus situations leading to child involvement. We then monitored changes in these measures in male rowers (N = 38) from Cambridge, UK, following a manipulated “win” or “loss” as a result of an indoor rowing contest. Baseline results revealed that men with heightened testosterone and SPMV values typically had greater inclinations toward engaging in casual sexual relationships and a higher likelihood of approaching attractive women in a hypothetical social situation. As anticipated, both testosterone and SPMV increased following a manipulated “victory” and were associated with heightened sociosexuality, and increased expectations toward approaching attractive women versus individuals who would involve them in interacting with children after the race. SPMV and self-esteem appeared to mediate some of the effects of testosterone on post-race values. These findings are considered in the broader context of individual trade-offs between mating and parental effort and a model of the concurrent and dynamic androgenic and psychological influences contributing to male reproductive effort and success. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12110-018-9323-5) contains supplementary material, which is available to authorized users.